2010
DOI: 10.1017/s0003055410000316
|View full text |Cite
|
Sign up to set email alerts
|

Leapfrog Representation and Extremism: A Study of American Voters and Their Members in Congress

Abstract: We consider the relationship between the preferences of American voters and the preferences of the U.S. legislators who represent them. Using an Internet-based, national opinion survey in conjunction with legislator voting records from the 109th and 110th Congresses, we show that members of Congress are more extreme than their constituents, i.e., that there is a lack of congruence between American voters and members of Congress. We also show that when a congressional legislator is replaced by a new member of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
302
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(319 citation statements)
references
References 59 publications
15
302
0
2
Order By: Relevance
“…[8] This result may also reflect the fact that, in some contexts, models of special interest and partisan politics may better explain Congressional voting than the median voter. [24] Individual preferences may change over the course of political debate, and further survey evidence will be necessary to update public opinion on clean energy deployment policies. At present, however, the difference between public opinion and political support that we find is consistent with the observation that a majority of Americans support clean energy and climate-change policies, while the necessary majorities in Congress do not.…”
mentioning
confidence: 99%
“…[8] This result may also reflect the fact that, in some contexts, models of special interest and partisan politics may better explain Congressional voting than the median voter. [24] Individual preferences may change over the course of political debate, and further survey evidence will be necessary to update public opinion on clean energy deployment policies. At present, however, the difference between public opinion and political support that we find is consistent with the observation that a majority of Americans support clean energy and climate-change policies, while the necessary majorities in Congress do not.…”
mentioning
confidence: 99%
“…The trend of primary electorates choosing extreme candidates could lead to a lack of ideological congruence between members of Congress and their general election constituencies (Bafumi and Herron, 2010) as moderate voters are disincentivized from voting (Callender and Wilson, 2007), thus further reinforcing recent trends towards political polarization among both elected officials and rank-and-file voters (Stone, Maisel and Lowman, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Primaries lack party cues and attract less media coverage, so they tend to attract more politically engaged, partisan, and ideologically extreme voters than do general elections (Kaufmann, Gimpel and Hoffman, 2003;Fiorina, Abrams and Pope, 2006;Abramowitz and Saunders, 2008). These primary voters may draw candidates' attention because elected officials tend to represent the interests of engaged constituents more than disengaged constituents (Bafumi and Herron, 2010;Burden, 2004).…”
Section: Candidates and Constituenciesmentioning
confidence: 99%
“…Poole andRosenthal (1997, 2007) were among the first to demonstrate measures of political ideology using IRT that went beyond party affiliation, when they generated estimates of ideology for members of Congress using a large number of floor votes. The ideology of bureaucratic agencies and federal secretaries have also been measured (Clinton et al 2012;Bertelli and Grose 2009;Chen and Johnson 2015), while others have used similar techniques to measure the political ideology of state legislatures (Shor and McCarty 2011), local elected officials (Connolly and Mason 2016), candidates for public office (Bonica 2013), and voters (Bafumi and Herron 2010). In the public sector, scholars have also sought to measure the political ideology of large public sector agencies (Clinton et al 2012;Bertelli and Grose 2009;Clinton and Lewis 2008;Chen and Johnson 2015), and others have attempted to measure the political ideology of "interest groups" (often nonprofit organizations) (Mason 2015;McKay 2008McKay , 2010Bonica 2013;Barber 2015;Poole and Rosenthal 2007).…”
Section: Measuring Political Ideologymentioning
confidence: 99%
“…Bonica (2013) demonstrated that Political Action Committees (PACs), those that provide funding for candidates running for office, are more ideologically moderate than Congress. Bafumi and Herron (2010) argued that voters are more ideologically moderate than those they've voted to send to Congress. Barber (2015) finds mixed results showing that PACs tend to be more moderate with their giving, while individual donors tend to support more extremist candidates for office.…”
Section: Findings and Consistency Checksmentioning
confidence: 99%